Tuning RGD motif and hyaluronan density to study integrin binding - Zapp, Cornelia; Minsky, Burcu Baykal; Böhm, Heike (Frontiers in physiology, 2018)
Well-controlled surfaces with immobilized substrates enable novel approaches to investigate specific aspects of biological processes related to cell adhesion or motility. A subset of integrins, cellular transmembrane glycoproteins, recognize the evolutionarily conserved tripeptide sequence RGD, and anchor cells to their surrounding proteins as well as mediate bidirectional signaling. In this study, the main question was how co-presentation of hyaluronan, an essential component of the extracellular matrix, and the RGD motif affect integrin binding. We report a method to prepare self-assembled monolayers on gold surfaces, co-presenting the cell adhesive RGD motif and small hyaluronan molecules, to investigate integrin containing proteoliposome binding. This technique enables an independent adjustment of the RGD motif and hyaluronan density while maintaining a passivating background.. Layer formation and subsequent interactions with αIIbβ3 integrins, which are reconstituted in liposomes, was monitored by label-free quartz crystal microbalance with dissipation monitoring (QCM-D). Exceeding a critical RGD motif density of 40% results in enhanced binding of proteoliposomes. Co-presentation studies with varying hyaluronan and constant RGD motif density demonstrate that marginal amounts of hyaluronan are sufficient to prevent integrin binding. These findings are of specific importance in relation to cancer cell microenvironment, which show highly enriched hyaluronan in the surrounding extracellular matrix to reduce adhesion properties.